Analysis of Mathematical Critical Thinking Skills Based on Students' Learning Styles in Junior High School - Kintoko Kintoko; Sri Wulandari; Deni Hadi Siswanto (Pendidikan Matematika STKIP Kusuma Negara, 2025)
Critical thinking is vital for learning statistics in mathematics. This study aims to evaluate the critical thinking abilities of eighth-grade students at Muhammadiyah Pakem Junior High School by considering their learning styles in the context of statistics. This qualitative research involved two students selected through purposive sampling as research subjects from each learning style: visual, auditory, and kinesthetic. Data were collected via questionnaires, tests, and interviews. The data processing techniques applied included data presentation, data reduction, and conclusion drawing. The research findings indicate that: (i) students with a visual learning style demonstrated exceptional critical thinking skills, aligning with the indicators of interpretation, analysis, evaluation, and inference; (ii) students with an auditory learning style exhibited strong abilities in evaluation, analysis, and inference, although their interpretation skills were not fully developed; and (iii) students with a kinesthetic learning style possessed good skills but had not yet fully met the indicators of analysis and evaluation. Furthermore, students with a visual learning style were considered more proficient in critical thinking, as they were able to explain visual representations of mathematical concepts before solving problems. On the other hand, auditory and kinesthetic learners still have the potential to further develop their critical thinking skills.